2013
DOI: 10.4236/as.2013.412094
|View full text |Cite
|
Sign up to set email alerts
|

The patterns and risks for disease spreading of cattle movement in China

Abstract: In order to reduce the risks for the spread of disease in cattle movements, we investigated China's cattle breeding and movement pattern, analyzed risk factors of disease infection caused by long-distance movement, explored the relevant risk management measures and conjectured the direction of cattle movement based on the regional distribution of cattle inventory and beef price. We also constructed a market value chain in live cattle movements and qualitatively analyzed the risks for unapparent infection in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
2
0
0
Order By: Relevance
“…The respondents who do not allow their animals to mingle with other cattle may be doing so to keep their animals free from any communicable diseases which they may encounter from other cattle. These findings are in close accordance with the observations of Sun [ 60 ] for disease spreading of cattle movement in China. While studies by Dereje [ 38 ] have indicated that most of the respondents allow their cattle to move with other herds which they think minimizes the chances of inbreeding in the herd.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The respondents who do not allow their animals to mingle with other cattle may be doing so to keep their animals free from any communicable diseases which they may encounter from other cattle. These findings are in close accordance with the observations of Sun [ 60 ] for disease spreading of cattle movement in China. While studies by Dereje [ 38 ] have indicated that most of the respondents allow their cattle to move with other herds which they think minimizes the chances of inbreeding in the herd.…”
Section: Resultssupporting
confidence: 93%
“…The study also indicates that the respondents from Mankush are strict when it comes to allowing their herd to mix with newer herds which are however not such strict true in the other two locations. The observations are in close accordance with the findings of Sun [ 60 ]. The mixing of the herds in Fanguso and Almahal areas takes place at the watering points.…”
Section: Resultssupporting
confidence: 93%